(untitled) (Research, Society and Development, 2026)
Introduction: Early Childhood Caries (ECC) is a multifactorial condition resulting from the interaction of biological, behavioral, dietary, and microbiological factors. Changes in salivary pH, flow rate, and buffering capacity directly influence the balance between enamel demineralization and remineralization, thereby modulating disease risk. In parallel, diets rich in sucrose favor the acid metabolism of Streptococcus mutans and Lactobacillus spp., the main bacteria associated with caries. This article aims to compile and analyze recent evidence on the biological (saliva, pH, buffering capacity, microbiome) and behavioral (diet, hygiene, habits) determinants involved in ECC, highlighting their implications for clinical practice in Pediatric Dentistry. Methodology: This review brings together recent studies that investigate the biological and behavioral determinants of early childhood caries, emphasizing the role of saliva, the oral microbiome, and diet as central factors in the etiology of the disease. Results and Discussion: The results of this review confirm that early childhood caries is a multifactorial condition arising from the dynamic interaction between biological, behavioral, and environmental factors. Findings related to salivary pH, buffering capacity, salivary flow, cariogenic diet, and the microbiome show significant consistency with what has been widely discussed in the international literature. Final Considerations: It is concluded that understanding the determinants of early childhood caries is essential for clinical practice in Pediatric Dentistry. The literature analyzed indicates that reducing caries prevalence depends primarily on early, educational interventions capable of modifying behaviors and restoring the ecological balance of the oral cavity.